Global interventions addressing student nurses’ absenteeism in clinical placement: a scoping review - Masutha, Thingahangwi Cecilia; Motadi, Selekane; Maluleke, Mary (Frontiers in Education, 2025)
IntroductionClinical placement is one of the critical aspects of nursing training; it allows students to gain first-hand experience by dealing with confirmed cases in clinical areas, and this helps them to put the theory they learned from the classroom into practice. Absenteeism from the clinical areas might affect the student’s progression to the next level of study.AimThis scoping review examined the current literature on interventions addressing student nurses’ absenteeism in clinical placement.MethodsA scoping review of the literature was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extension for Scoping Reviews (PRISMA-ScR). Various databases were used for searching for the relevant articles and were handled in the reference manager EndNote. Ten research studies from global countries were included in this review. Primary data were synthesized using descriptive analysis methodology.FindingsThe findings indicated the available interventions to address student nurses’ absenteeism: (1) adequate clinical accompaniment and supervision, (2) students’ support, and (3) students’ motivation.ConclusionBy fostering better support systems and recognizing student commitment, healthcare institutions can enhance attendance rates and overall clinical experiences, ultimately contributing to developing competent, motivated healthcare professionals.